Sotto le Nuvole, sotto la Foresta: applicazioni Tecnologiche Lidar e di Intelligenza Artificiale per Nuove prospettive nel Sito monumentale di Kuelap - Perú - Righetti, Giovanni; Serafini, Stefano; Brondi Rueda, Fabian; Church, Warren; Garnero, Gabriele (Archeomatica, 2020)
MEDS BV, a company based in the Netherlands but mainly active in the Americas, perform an aerial LiDAR and photogrammetric survey in November 2019 at the archaeological site of Kuelap, on the northeastern Peruvian cordillera at about 3000 m altitude (Amazonas region). Although the monumental Kuelap site complex is immense and was likely the most populous settlement in the Utcubamba river valley, the site and its occupants are not described in any known documents left by the early Spanish colonists. Consequently, and despite intensive archaeological studies, important questions regarding Kuelap's political, economic, and religious roles in the region remain unresolved. The work has the logistical support of the IGN, Instituto Geográfico Nacional of Peru, and avails itself of the collaboration of anthropologist Warren Church, a specialist in ancient Andean cultures and expert in the archaeology of the region under study.